Assessment of source material for malting barley breeding - O. A. Yusova; P. N. Nikolaev; M. A. Kuzmich; L. S. Kuzmich (Труды по прикладной ботанике, генетике и селекции)
Background. The objective of the research was to identify promising genotypes of malting barley in the source material developed at Omsk Agricultural Scientific Center.Material and methods. The studies were carried out from 2017 to 2020. in the southern forest-steppe of Western Siberia. The target material included 13 lines: Sasha × Getman (2 lines), Sasha × Margret, Podarok Sibiri × Getman (3 lines), Omsky 95 × Beatrice (3 lines), Omsky 95 × Despina, Omsky 95 × Viva, Omsky 100 × Margret, and Omsky 90 × Margret. Biochemical assessment of grain quality for brewing qualities was carried out jointly with Nemchinovka Federal Research Center according to GOST 5060-86 (Bаrley for brewing. Specifications).Results and discussion. The most promising were the lines demonstrating increased yield (5.39–6.21 t/ha) and reduced mass fraction of protein (11.39–11.92%): Sasha × Getman (1), Sasha × Getman (2), Omsky 90 × Margret, Omsky 95 × Beatrice (2), Omsky 95 × Beatrice (3), and Omsky 95 × Despina. Besides, these lines had a set of the following brewing characteristics: grain evenness (98.7–99.95); grain filminess (9.3–9.9%), 1000 grain weight (55.6–57.0 g), grain extractivity (78.1 and 78.9%), mass fraction of starch (55,35–56.83%), color (0.15–0.30 EBC units), and malt vitreousness (0.0–3.0%).Conclusion., The lines Sasha × Getman (1) and (2), Omsky 90 × Margret, Omsky 95 × Beatrice (2) and (3), Omsky 95 × Despina are recommended for further research.